Desmoplastic ameloblastoma: a rare odontogenic neoplasm with unusual radiographic and histomorphological presentation - Belgaumi, U I (BMJ Publishing Group, 2013)
Desmoplastic ameloblastoma (DA) is a newly recognised, rare odontogenic neoplasm that is a histological variant of ameloblastoma. In this type, the islands of ameloblastoma are surrounded and often compressed by a dense and sometimes hyalinised fibrous connective tissue. Although ameloblastomas are usually located in the mandible, this variant often occurs in the anterior maxilla. In view of the paucity of DA case series and only limited understanding of its biological behaviour and prognosis, proper treatment strategies for DA are not entirely defined so far. The purpose of this paper was to review the literature and to demonstrate a rare case for an improved understanding of the behaviour and prognosis of DA.